Pengaruh Beban Kerja Dan Stress Kerja Terhadap Employee Mental Health Di Mediasi Work-Life Balance Di PT. Bumi Maestroayu (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of cultural environmental factors and psychological empowerment on employee engagement, with employee perspectives serving as a mediating variable. The research employs a quantitative approach using a causal-explanatory method and data analysis through PLS-SEM 4.0. The population in this study consists of 100 employees, and the respondents are 100 individuals working at PT. Bumi Maestroayu, selected randomly using the Simple Random Sampling method. The study reveals that workload has a negative effect on employees' mental health but does not have a direct impact on work-life balance. Conversely, employees' mental health is proven to have a positive effect on work-life balance. Job stress has a positive influence on mental health and also directly contributes to the improvement of work-life balance. Furthermore, mental health is proven to mediate the influence of workload and job stress on work-life balance. These results emphasize the importance of maintaining employees’ mental health as a key factor in creating a balance between personal and professional life.
Keywords: Workload, Stres Kerja, Kesehatan Mental Karyawan, Work-Life Balance